Posttraumatic and Comorbid Stress Reactions of Children with Different Severity of Traumatization by the War - Vizek-Vidović, Vlasta (Array, 1997)
The study examines affective and behavioral symptomatology of two groups of children being to a different degree multiply traumatized during the war against Croatia. Group of more traumatized children consisted of 387 children who experienced 9 and more traumatic and stressful war events. Group of less traumatized children consisted of children who experienced 8 and less of those events (N=647). Sample comprises 573 girls and 497 boys from school grade 2 to 8 (age 8 to 16 years). Children from grade 2 to 5 were grouped as younger (N=467) and children from grade 6-8 were grouped as older children (N=567). Six self-reported questionnaires were used to assess number and type of survived war experiences, PTSD symptoms, anxiety, depression, psychosomatic symptoms and psychosocial adaptation. The performed canonical discriminant analysis yielded significant discriminant function that indicates moderate differentiation between the two groups of children according to the assessed symptoms. Results of the 2x2x2 ANOVAs (gender x age x level of traumatization) indicate that children s reactions to war traumata vary in respect to all those factors, and their interaction. Results indicate that gender differences are more prominent in older children. Older girls report more posttraumatic stress reactions, anxiety and depression, but also it seems that they are better adapted than boys. Younger children, particularly those who survived more war events, report more PTSD symptoms than older children.